The combined effects of VPD and soil moisture on historical maize yield and prediction in China - Zhao, Fujie; Wang, Guojie; Li, Shijie; Hagan, Daniel Fiifi Tawia; Ullah, Waheed (Frontiers in Environmental Science, 2023)
Understanding the effects of thermal and water stress on maize yield in the context of climate change is crucial to ensure food security in China. However, very few studies looked into the combined effects of heat and water stress on maize yield in China. Here, we utilized historical reanalysis data from ERA5 and four future shared socioeconomic pathway scenarios (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5) of the Coupled Model Intercomparison Project 6 (CMIP6) models to predict the maize yield. We used the linear mixed-effects model to quantify the grid cell sensitivity of vapor pressure deficit (VPD) and root-zone soil moisture to maize yield in China during 2010-2016. The results infer that VPD and root-zone soil moisture are excellent representatives of heat and moisture stress. Maize yield is beneficial only when the atmospheric moisture demand and soil moisture are in relative balance. Based on the historical results’ polynomial function for VPD and soil moisture, we predict the maize yield response to soil moisture and VPD in the four SSPs. The results show that considering soil moisture in the future the projected yield estimates reduce the overestimated yield loss by half compared to considering only atmospheric moisture requirements. Maize yield will decrease under representative SSPs due to an increase in temperature (1.5, 2.0, 2.5, 3.0, 3.5, 3.5, and 4.0°C). This study suggests that both atmospheric moisture demand and supply need to be considered when analyzing the specific influence of climate change on crop yield to secure and assure global food supplies.